How can Fox Networks Group grow faster via entering and thriving in the online advertising market? Communications plan for this is Fox - Pereira, Daniela Costa (2020)
The current advertising landscape in Portugal reveals that the Pay- TV market has reached maturity giving little margin for growth while digital has been the advertising channel with the biggest growth. Being FNG’s main business in the Pay- TV market, the company plans to invest in new Digital advertising solutions to keep ahead with the advertising landscape. An analysis of the advertising market comprising a primary and secondary research followed by a marketing and communications plan allowed to develop This is Foxas the solution for FNG to thrive in the online advertising market increasing by 1225% the online advertising revenue.